Leveraging TikTok for Digital Daʿwah: Assessing Its Influence on Anti-Vaping Norms Among Malaysian University Students (Contrarius Series: Law & Social Justice, 2026)
Amidst the escalating global health crisis of e-cigarette consumption, this study critically examines the intersection of religious digital outreach and health-seeking behavior s among university students. While conventional public health campaigns often struggle to resonate with tech-savvy demographics, this research investigates the potency of "Digital Daʿwah" on TikTok as a transformative medium for fostering anti-vaping attitudes. Utilizing a robust quantitative framework, a survey was administered to 300 undergraduate students across Malaysian public universities, yielding 278 valid responses for rigorous analysis. The research instrument was meticulously designed to interrogate the complex nexus between theological literacy—specifically the Islamic fatwa on vaping—health risk perception, and digital consumption patterns on short-form video platforms. Empirical findings, analyzed through descriptive and inferential statistics, underscore a profound cognitive dissonance within the youth demographic. Despite a near-universal recognition of vaping’s health hazards (95.3%) and its haram(prohibited) status (89.9%), experimentation remains high at 40.3%, with a stark prevalence among male students (56.3%) compared to females (18.6%; p < 0.001). However, the data reveals a pivotal shift in receptivity; students demonstrate a significant preference for the creative, informal, and "humanized" delivery of religious messaging on TikTok (M=4.15) over traditional, didactic pedagogical methods. Interestingly, no significant gender disparity was found in the acceptance of these digital interventions (p=0.514), suggesting a universal appeal of "edutainment" styles for behavior al change. By conceptualizing digital daʿwah as a sophisticated form of health communication, this study offers a novel theoretical contribution to the international discourse on social media and preventive medicine. It provides a scalable framework for global health authorities and religious stakeholders to leverage algorithmic media aesthetics in mediating health-conscious norms within multicultural societies. Ultimately, the research underscores that in the digital era, the efficacy of religious messaging is predicated not only on theological accuracy but on its strategic alignment with the sociocultural rhythms and visual language of social media platforms.